Development of Information System TEPRA in Administrations Development Gianyar Regency Using Rapid Application Development Model - I Made Oka Semara Putra (International Journal of Engineering and Emerging Technology, 2021)
The development of information technology that has developed in government is very helpful in the process of managing government infrastructure. Included in the Gianyar Regency Development Section which has implemented or applied a system, namely the TEPRA System. The TEPRA system is a system used to carry out the process of monitoring the realization of the budget given to each OPD (Regional Apparatus Organization) in Gianyar Regency to find out any problems or obstacles that might occur when realizing the work program of each related OPD. The frequent mistakes made by Tepra Operators in completing data information about the work program of the relevant OPDs are the reason that it is necessary to carry out the process of developing a tepra information system application. In the development process, the Rapid Application Development model is used to get the design that is expected based on the results of the audit which are used for reference in the tepra information system development process.